The HLA-DR Expression on Monocytes in Acute Dengue Infection - Umi Solekhah Intansari; Muhammad Ilham Bin Azib; Mohd Nazirul Shareef bin Mohd Ridhwan; Ida Safitri Laksanawati (Tropical Medicine Journal, 2012)
Introduction: Dengue is the most common disease of mosquito-borne infection. According to the World Health Organization, it is estimated that 50 million cases ofdengue infection have been reported annually. Macrophages andmonocyte are thought to play an important role in dengue infection both as primary targets of viral infection and as a source of immunomodulatory cytokines.Whenmonocytes are infectedby dengue viruses, it processed the virus by lyses it and expressed the antigen on its surfacemembrane bind together with HLA class II molecules. HLA-DR-expressing monocytes in acute dengue patientsespecially the intensity is still poorly understood.Measurement of at difference days of infectionwill give an evidence about the role ofmonocytes in dengue pathogenesisObjectives: To observe the kinetics on percentage of HLA-DR expressingmonocytes and themedian of HLA-DR expression intensity in acute dengue infection.Methods: This researchwas an observational type study conducted by cross sectionalmethod towards all the dengue patients in Dr. Sardjito’s General Hospital. Blood samples were drawn from 32 acute dengue infected patients from Day 1 to Day 6th. The HLA-DR expression was measured flow cytometrically using FACS Calibur.Results: The data showed that the mean difference in acute dengue infection from Day 1 to Day 6 is not significant with the p-value larger than 0.05, (p>0.05).Conclusion: The peak level of activated HLA-DR monocyte was at day 2 and then decreasing until day 6. There were no significant changes in percentage of HLA-DR-expressing monocytes from the day 1 to the day 6 and the median intensity of HLA-DR expression in acute dengue infection.Keywords HLA-DR-expressing monocytes, Acute Dengue Infection